POYEKSI DAYA DUKUNG LAHAN TERHADAP KEBUTUHAN RUMAH DI KOTA TANGERANG SELATAN (PROJECTION POWER NEEDS TO SUPPORT LAND HOUSE IN THE CITY OF SOUTH TANGERANG) - Iriani, Lia Yulia (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2016)
ABSTRACTSouth Tangerang city with an area of 147.19 km2, a total population of 1.40517 million inhabitants, the rate of growth of population of 3.63% per year. (BPS. 2014). This has resulted in an increase in the needs of housing, especially in urban areas, reaching 33,562 housing units. The highest number of backlog is in district of East Ciputat, 9,612 units as Pamulang 8,131 units, while for the smallest there is in Serpong amounting to 375 units. This condition requires a land, where the land use data in South Tangerang City mostly for housing and settlements are an area of 8.804.17 ha or 65.88% of 14.719 hectares. This raises problems of the city development is not balanced with the availability of land and high land prices. The Increased needs of the home, causing a decrease in the carrying capacity of the land. The research objective linkage mapping the housing needs of increasing the carrying capacity of the land. Descriptive research method through a case study approach and explanatory research draft, to analyze the relationship between one variable with another variable or how a variable affects the other variable. The expected results as policy recommendations for local authorities in the preparation of the development policy of housing and settlements.Keywords: backlog , land, housing and settlement, policy, local governments ABSTRAKKota Tangerang Selatan dengan luas 147,19 Km2, jumlah penduduk 1.405.170 jiwa, laju pertumbuhan penduduk sebesar 3,63% /tahun. (BPS.2014). Hal ini mengakibatkan peningkatan kebutuhan rumah terutama di perkotaan, mencapai 33.562 unit rumah. jumlah backlog tertinggi di Kecamatan Ciputat Timur sebanyak 9.612 unit, Kecamatan Pamulang 8.131 unit, sedangkan untuk backlog terkecil terdapat di Kecamatan Serpong yaitu 375 unit. Kondisi ini memerlukan lahan, dimana data penggunaan lahan di Kota Tangerang Selatan sebagian besar adalah untuk perumahan dan permukiman yaitu seluas 8.804.17 Ha atau 65,88 % dari 14.719 Ha. Hal ini menimbulkan permasalahan yaitu perkembangan kota yang tidak seimbang dengan ketersediaan lahan dan harga lahan yang tinggi. Peningkatan kebutuhan rumah, menyebabkan penurunan daya dukung lahan. Tujuan penelitian memetakan keterkaitan kebutuhan rumah yang semakin meningkat terhadap daya dukung lahan, Metode penelitian secara deskriptif melalui pendekatan studi kasus (case study approach), rancangan penelitian eksplanatori, untuk menganalisis hubungan antara satu variabel dengan variabel lainnya atau bagaimana suatu variabel mempengaruhi variabel lainnya. Hasil yang diharapkan sebagai rekomendasi kebijakan bagi pemerintah daerah dalam penyusunan kebijakan pengembangan perumahan dan permukiman.Kata Kunci: Kebutuhan rumah, lahan, perumahan dan permukiman, kebijakan, pemerintah daerah